An expansion and reconstruction project case for the leachate treatment station in Handan - ZHU Haidong; ZHU Weibing (Gongye shui chuli)
Due to the rapid increase of landfill volume and the aging and damage of the leachate treatment facilities at a landfill in Handan, the original leachate treatment station at the landfill could not meet the existing leachate treatment needs. The combined process of “pretreatment+external MBR+nanofiltration(NF)+reverse osmosis(RO)” was adopted to expand and reconstruct the original leachate treatment station,and a new nanofiltration concentration reduction system was built. The “material membrane reduction+humic acid extraction” process was adopted to achieve concentration reduction treatment. The problems of tight schedules, compact sites, and shortage of funds were effectively solved through rational layout, reconstruction of old buildings, and construction of new steel tanks. After the expansion and reconstruction, the treatment capacity of the leachate treatment station was 500 m³/d with the yield of effluent clear liquid as 95%. The effluent water quality stably met the emission standard of Table 2 in the “Standard for Pollution Control on the Landfill Site of Municipal Solid Waste”(GB 16889‒2008). The total investment for the project was 22.18 million yuan, and the actual operating cost of the renovated leachate treatment station was 41.82 yuan/m3.